Influencing Factors of the Continuous Usage Intention of Consumers of Online Food Delivery Platform Based on an Information System Success Model - Wang, Junbin; Shen, Xiangdong; Huang, Xinbei; Liu, Yuting (Frontiers in Psychology, 2021)
Online food delivery (OFD) has gradually become a development trend in the catering industry. However, the homogenization of the principal OFD platforms is becoming increasingly obvious, and there is an urgent need to explore the continuous usage intentions of consumers of the OFD platform. Unlike previous studies, this study employs DeLone and McLean's information system (IS) success model as the theoretical framework and constructs the influencing factors model of the continued usage intentions of users of the OFD platform from three aspects, namely, service, system, and information quality. Participants (N = 361) completed a questionnaire assessing their continuous usage intentions of the OFD platform, and the results were analyzed using a structural equation model (SEM). Service worker, platform quality, and content consistency have significant positive effects on the trust in the platform and satisfaction of consumers. Both the trust in the platform and satisfaction of consumers have a positive impact on their continuous usage intentions. We also explored the mediating effect of the trust in the platform and satisfaction of consumers. This study adds to the academic literature and practical implications for the continuous usage intention of consumers. This study discusses the influencing factors and formation mechanism of the continuous usage intention of consumers and proposes a model of the continuous usage intention of consumers of OFD platforms. Moreover, OFD platforms can make differentiation strategies more targeted and eliminate the dilemma of homogenization competition of OFD platforms.